Determination the role of risk factor in neonatal jaundice disease at AL- Nasiriya city (University of Thi-Qar Journal of Science, 2015)
Descriptive study was carried out to assess of neonatal jaundice in the sample consist of 150 patients selected fromBent – AL Huda hospital during ( 1- 10 -201 2 ) to ( 1- 10 -2013 ). Neonatal jaundice measured by application ofquestioners that designed by researchers themselves collected through personal interview of patients family as mean of data collection through use statistically tool( frequent, percentage , X2 ) and through use in program SPSS- V15 to analysis data . The aim from the study is to determine risk factor of neonatal jaundice. The result revealed the incidence of neonatal jaundice more in the male , low birth weight , NVD, breast feed , mother did not receive Anti – D finally the main recommendation should be monitor after birth the neonate have risk factor of jaundice .